Il passaggio dalla causa di nullità matrimoniale al procedimento di scioglimento del matrimonio non consumato secondo il can. 1678, § 4 (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione - 2. La progressiva semplificazione normativa del passaggio alla via amministrativa - 3. La clausola “de consensu partium” del can. 1681 - 4. Interrelazioni tra processo di nullità e procedimento di scioglimento - 5. L’interpretazione del nuovo can. 1678, § 4 - 6. La decisione del tribunale in caso di disaccordo tra le parti circa il passaggio alla via amministrativa - 7. Una proposta de iure condendo.The transition from the marriage nullity case to dissolution of non-consummated marriage procedure according to can. 1678, § 4 *ABSTRACT: The Motu proprio Mitis Iudex Dominus Iesus has simplified the transition from a marriage nullity case in progress to that of dissolution of non-consummated procedure: it is no more required that the parties consent to but that they be heard. After a brief historical excursus on the subject, starting from the Pius-Benedictine Code, the study aims, first, at understanding the underlying rationale of the new provision of canon 1678 § 4, and then at exploring the concrete ways in which it is to be applied, especially in the event of disagreement between the parties on the transition. Finally, on the basis of the praxis of the Tribunal of the Roman Rota, de iure condendo a proposal is made.